2017
DOI: 10.1177/0040517516685276
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface hydrophilicity on the adhesion properties of wet fabrics or films to water

Abstract: The adherence of wet fabrics to the skin brings much discomfort. The relationship between hydrophilicity and adhesion properties of fabric materials is investigated. A theoretical expression is given to describe the relationship of adhesion force, water contact angle (WCA), and radius of fabric–liquid interface. The adhesion force grows with decreasing WCA and increasing radius of the fabric–liquid interface. With the help of atmospheric pressure plasma jet (APPJ) treatment, the hydrophilicity of the fabric ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…On one hand, the friction force between the skin and wet fabric with no cover weight was commonly larger than the adhesion force. The adhesion force between the skin and completely soaked samples (120 mm × 120 mm) ranged from 0.06 N to 0.2 N (Lou et al., 2015, 2017, 2018), while the friction force between the skin and wet samples (120 mm × 60 mm) with no cover weight ranged from 0.5 N to 2 N (Tang, Chau, Kan, & Fan, 2018a). This indicates that the friction mode causes a greater skin deformation due to the larger force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, the friction force between the skin and wet fabric with no cover weight was commonly larger than the adhesion force. The adhesion force between the skin and completely soaked samples (120 mm × 120 mm) ranged from 0.06 N to 0.2 N (Lou et al., 2015, 2017, 2018), while the friction force between the skin and wet samples (120 mm × 60 mm) with no cover weight ranged from 0.5 N to 2 N (Tang, Chau, Kan, & Fan, 2018a). This indicates that the friction mode causes a greater skin deformation due to the larger force.…”
Section: Resultsmentioning
confidence: 99%
“…No significant correlation is found between the top surface wetting time and SP under two adhesion-separation conditions (ASLV: r ¼ À.047, p > .05; ASHV: r ¼ À.074, p > .05). Lou et al (2018) suggested that a longer wetting time with a lower surface energy gave a smaller adhesion force at the fabric-water interface. However, this change was not found, which may have been due to the different amounts of water remaining on the fabric surface in the study.…”
Section: Effect Of Fabric Propertiesmentioning
confidence: 99%
“…Additionally, the frictional, geometrical, and other characteristics of the solid surface all affect the adherence of soil to solids. Several studies have shown that solid materials with high surface free energy and good hydrophilicity strongly adhere [15][16][17]. The adherence of soil to solids can also be influenced by environmental factors such as process pressure, temperature, etc.…”
Section: Introductionmentioning
confidence: 99%